SPOKEN LANGUAGE FEATURES GENERATED BY PLAY-BASED INSTRUCTIONS (Universitas Negeri Semarang, 2013)
Penelitian ini mengenai fungsi tuturan bahasa Inggris yang dikuasai oleh anakanaktaman kanak-kanak Mondial Education Semarang Tahan Ajaran 2012.Peneletian ini bertujuan mengungkap fungsi tuturan apa yang dikembangkan anakanaktersebut melalui pengalaman belajar mereka dan bagaimana tuturan tersebutdihasilkan. Data penelitian ini dikumpulkan dengan mengamati dan merekamfungsi tuturan yang dihasilkan anak-anak melalui sejumlah kegiatan belajarmereka. Data yang direkam kemudian ditranskripsi berdasar giliran bicara untukmengidentifikasi pengalaman belajar mereka dan mengkategori ujaran merekaberdasar model Kompetensi Tindak Tutur Celce Murcia (1995). Interpretasi temuandilakukan dengan merujuk pada teori Akuisisi Bahasa Kedua, teori pelajar bahasausia dini dan teori-teori lain yang relevan. Hasil penelitian menunjukkan, anakanakterlibat dalam sejumlah kegiatan belajar seperti drama, pusat matematika,pusat alam dan blok-blok permainan. Pengalaman belajar tersebut mendorong anakmelahirkan ujaran-ujaran fungsi bahasa Inggris meliputi tujuh ranah kunci yaknipertukaran interpersonal, informasi, opini, perasaan, suasi, masalah dan skenarionmasa mendatangThis study is concerned with the speech functions acquired by kindergarten children throughtheir learning experiences. The object of the study is the children of kindergarten level of MondialEducation Semarang in 2012 Academic Year. The goal of the study is to find out whatspeech functions are developed by the children through their learning experiences and howtheir utterances are generated. The data were collected by observing and recording the children’sproduction of language functions in a number of activities of their learning experience.The recorded data were then transcribed based on turn to identify the learning experience andcategorize the children utterances based on Celce-Murcia’s (1995) proposed model of ActionalCompetence. The interpretation on the findings is conducted in the light of Second LanguageAcquisition, young learners and other relevant theories. The findings of this study show thatthe children were involved in a number of activities such as dramatic play, mathematic center,nature center and playing blocks. Those learning experiences have encouraged the children toproduce utterances of language functions which cover seven key areas namely interpersonalexchange, information, opinions, feelings, suasion, problems and future scenarios